A novel polynary fatty acid/sludge ceramsite composite phase change materials and its applications in building energy conservation. (April 2015) - He, Hongtao; Zhao, Pin; Yue, Qinyan; Gao, Baoyu; Yue, Dongting; Li, Qian
Abstract: The preparation and characteristics of a composite phase change material (PCM) produced by incorporating polynary fatty acid eutectic mixture into sludge ceramsite were studied. According to Schröeder–Van Laar equation, five different kinds of polynary fatty acid eutectic mixture were prepared, and one of them, suitable for regulating room temperature, was absorbed into sludge ceramsite by vacuum impregnation method. The microstructures were observed by scanning electron microscope (SEM). The thermal properties and chemical structures were analyzed by differential scanning calorimetry (DSC) and Fourier transform infrared (FT-IR) spectrometer, respectively. The durability or stability of the composite PCM was determined by heating–cooling cycles test, and the temperature regulation effect was tested by building models. The results indicated that polynary fatty acid eutectic mixture can be retained by 46 wt.% into the pores of sludge ceramsite without seepage. The melting temperature of composite PCM was 26.66 °C, and the corresponding melting enthalpy was 47.1 J/g, suitable to regulate building room temperature. The preparation of composite PCM was just a physical combination, and its chemical structures can remain stable in application process. In addition, model experiments showed that the prepared composite PCM can significantly reduce indoor temperature fluctuation, suitable for building energy conservation. Highlights: A series of fatty acids mixtures were prepared by heating-ultrasonic method. A novel polynary fatty acid/sludge ceramsite composite PCM was characterized. The theoretical data was obtained by Schröeder Van Laar equation. The durability of the composite PCM was determined by heating–cooling cycles test. The temperature regulation effect was tested by building models.